The complete mitochondrial genome of the Korean endemic millipede Anaulaciulus koreanus (Verhoeff, 1937), with notes on the gene arrangement of millipede orders - Woo, Hyung Jik; Nguyen, Anh D.; Jang, Kuem Hee; Choi, Eun Hwa; Ryu, Shi Hyun; Hwang, Ui Wook (Zootaxa, 2017)
The millipede Anaulaciulus koreanus (Verhoeff, 1937), belonging to the family Julidae, is an endemic species of the Korean fauna. In this study, we sequence and annotate the mitochondrial genome of A. koreanus. The complete mitochondrial genome of this species is 14,916 bp in length and contains 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes (16S and 12S rRNA), and a large non-coding region. The genome has a very high A+T content (71.1%), less than of the species Brachycybe lecontii Wood, 1864 (order Platydesmida; 76.6%) and Sphaerotheriidae sp. (order Sphaerotheriida; 71.2%). In comparison with the mitochondrial gene arrangement of eight other millipede species, the whole mitochondrial gene arrangement of A. koreanus is most similar to the nemasomatid species, Antrokoreana gracilipes Verhoeff, 1938, but differs from those of the other diplopod orders. The absence of tRNACys between the ND2 and COI regions is unique to the order Polydesmida, whereas the translocation of tRNATyr to between ND2 and COI is exclusive to the Sphaerotheriida. It is also shown that the translocation of tRNAThr between ND4L and ND1 may be a synapomorphy to support a close relationship of two orders Spirobolida and Spirostreptida.